The Ugnayan ng Pahinungod Roving Library - Marcelino, Neomi T.; Faderon, Rosalie B. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2002)
This thesis was undertaken for the purposes of evaluating the existing collection and services being offered by the University of the Philippines Roving Library in Diliman, Quezon City. It also sought to suggest ways on how to improve the collection and services of the program through the establishment of a library that will house its collection. The concept of the bookmobile started in the United States. But here in the Philippines, we have our own counterparts. The Museo Pambata Foundation's Bookmobile and the National Bookstores Buklat-aklat Bookmobile are just two among others. Here, in our very own University of the Philippines, we have the Roving Library administered by the Ugnayan ng Pahinungod Diliman Chapter.
During the study, questionnaires were distributed to volunteers who were students in UP taking up various courses. Interviews were also administered with the children participants from the Pook Ricarte, Palaris, and Dagohoy. The volunteers, mostly female, were students of UP Diliman who were required to render volunteer service to the program as a subject requirement. After a full semester of being volunteers, they realized the urgent need to improve the collection owned by the Roving Library, establish a fixed-site library, and acquire an appropriate vehicle to be used to transport the learning materials to the children of RIPADA.
The Roving Library proved to be of help bringing the magic of the printed page to the children of RIPADA, but certain impeding factors such as inadequate collection, lack of transportation, equipment, and building to serve as fixed-site library, and insufficient funds to sustain its continued operation were identified. There is an urgent need to conduct a university-wide campaign on the importance of the Roving Library to encourage students and university faculties to help in the Roving Library operations. It is also necessary that the collection of the Roving Library be organized. Practicum students from UP Institute of Library Science can be of help in organizing the collection and manning the fixed-site library.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines Ugnayan ng Pahinungod; Traveling library